Vulnerable parafoveal microcirculation quadrant in patients with type 2 diabetes mellitus - Chen-Yu Lin; Yi-Jing Sheen; Hsian-Min Chen; Yi-An Lu; Jun-Peng Chen; Hsuan-En Huang; Yu-Ju Lin; Peng-Tai Tien; Chia-Jen Chang; Hui-Ju Lin; I-Jong Wang; Chien-Chih Chou (Scientific Reports)
Abstract Diabetic retinopathy (DR) is a leading cause of vision loss among adults. This study evaluates Optical Coherence Tomography Angiography (OCTA) vessel density (VD) as a marker for DR in diabetes mellitus (DM) patients. An observational study was conducted with 47 type 2 DM patients and 21 healthy controls. OCTA measured superficial and deep retinal VD in the parafoveal region. Statistical analyses, including logistic regression and ROC curve analysis, were used to assess the association between VD and DR presence. Results showed that DM patients had lower parafoveal superficial (46.73 vs. 52.37%, p = 0.002) and deep VD (50.35 vs. 54.26%, p = 0.019) compared to controls. Within the DM group, DR patients had lower VD in the superior parafoveal superficial layer (p = 0.042) and temporal parafoveal deep layer (p = 0.035). ROC analysis identified a cutoff of 51.86% for the temporal deep parafoveal VD, with an AUC of 0.697 (p = 0.035) and 81.8% sensitivity for DR discrimination. Reduced VD in the temporal deep parafoveal region is linked to a higher DR likelihood. OCTA-derived VD metrics offer promise for early DR detection and underscore the importance of monitoring vascular changes in DM patients.